Fatigue-induced alterations in jump-landing biomechanics and knee injury risk in volleyball - Rudyanto Rudyanto; ifdil ifdil; Allysa Kholila Razak (JRTI (Jurnal Riset Tindakan Indonesia), 2025)
Volleyball involves frequent jumping and landing actions that place substantial mechanical stress on the lower extremities, particularly the knee joint, thereby increasing the risk of anterior cruciate ligament (ACL) and other knee-related injuries. This systematic review aimed to synthesize current evidence regarding biomechanical risk factors, fatigue-related alterations, neuromuscular control deficits, and preventive interventions associated with knee injury risk during volleyball jump-landing activities. A systematic literature search was conducted in the Scopus database following PRISMA 2020 guidelines. Ten studies published between 2020 and 2025 met the inclusion criteria and were included in the review. The findings showed that fatigue-induced biomechanical alterations, particularly increased dynamic knee valgus and reduced neuromuscular control, were the most frequently reported risk factors associated with knee injury mechanisms during volleyball jump-landing tasks. Evidence further indicated that neuromuscular training, dynamic taping, feedback-based interventions, and Pilates conditioning effectively improved landing mechanics and reduced injury risk indicators. Overall, knee injury risk in volleyball appears to be multifactorial, involving biomechanical, neuromuscular, cognitive, and fatigue-related mechanisms. These findings support the implementation of multidimensional injury-prevention programs and provide direction for future volleyball-specific biomechanical research.